Trade Liberalization and Wage Inequality : Evidence From India - Mishra, Prachi (IMF Working Papers; Working Paper ;, 2005)
We evaluate empirically the impact of the dramatic 1991 trade liberalization in India on the industry wage structure. The empirical strategy uses variation in industry wage premiums and trade policy across industries and over time. In contrast to earlier studies on developing countries, we find a strong, negative, and robust relationship between changes in trade policy and changes in industry wage premiums over time. The results are consistent with liberalization-induced productivity increases at the firm level, which get passed on to industry wages. Since tariff reductions were proportionately larger in sectors that employ a larger share of unskilled workers, the increase in wage premiums in these sectors implies that unskilled workers experienced an increase in their relative incomes. Thus, our findings suggest that trade liberalization has led to decreased wage inequality in India.